2017
DOI: 10.1080/10520295.2017.1303194
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of irisin in mole rats(Spalax leucodon)

Abstract: Irisin was first identified in skeletal muscle cells. It is an exercise protein that is secreted into the circulation; it causes conversion of white adipose tissue to brown adipose tissue. We investigated irisin immunoreactivity in mole rat (Spalax leucodon) tissues. We examined cerebellum, pituitary, heart, liver, pancreas, spleen, uterus, kidney and striated muscle in female adult mole rats. Tissues were processed, embedded in paraffin, sectioned at 5 μm and stained immunohistochemically for irisin. Irisin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Irisin is cleaved from fibronectin type III domain containing 5 (FNDC5), a transmembrane precursor protein expressed in muscle under the control of PGC-1α. FNDC5 is also known to be profoundly expressed in many regions of thebrain, including cerebellar Purkinje cells, the hypothalamus, and the hippocampus, a region of the brain involved in memory and spatial awareness [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Irisin is cleaved from fibronectin type III domain containing 5 (FNDC5), a transmembrane precursor protein expressed in muscle under the control of PGC-1α. FNDC5 is also known to be profoundly expressed in many regions of thebrain, including cerebellar Purkinje cells, the hypothalamus, and the hippocampus, a region of the brain involved in memory and spatial awareness [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These clinical findings are supported by experimental data showing abnormally reduced FNDC5 and PGC-1α expression in skeletal muscle from rats with HFrEF secondary to ischemic cardiomyopathy [42]. Irisin can also be produced by the heart [43]. Compared with wild-type animals, Fndc5 gene deletion resulted in exacerbation of LV hypertrophy, dysfunction and fibrosis, whereas Fndc5 gene overexpression resulted in attenuation of these phenotypes [44].…”
Section: Dysregulation Of Myokines In Hfmentioning
confidence: 65%
“…Existing evidence of the role of biological factors, such as leptin, insulin and adiponectin, whose main function is to regulate energy metabolism, in reproduction is conclusive [7,8]. Moreover, studies have shown that the expression of irisin has been identified in endometrium and ovary [9,10]. Based on these studies, we speculate that, irisin, a new molecular marker and target in metabolic disorder [11], may have potential effect on reproductive capacity.…”
Section: Introductionmentioning
confidence: 79%
“…Studies demonstrated that the expression of irisin has been found in endometrium and endometrial irisin level in PCOS patients decreased [9,10], which indicated a potential direct role of irisin on endometrium. Embryo implantation is the premise of successful pregnancy, it is crucial to take timely modifications for endometrium to become receptive to the developing embryo for success of implantation [12].…”
Section: Discussionmentioning
confidence: 99%